2016
DOI: 10.1159/000454858
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Peripherally Inserted Central Catheter in Amyotrophic Lateral Sclerosis Patients at a Later Stage

Abstract: Background/Aims: To describe the use of peripherally inserted central catheter (PICC), in amyotrophic lateral sclerosis (ALS) at a later stage. Methods: Twenty-five ALS patients in the later stages of the disease underwent PICC insertion followed by parenteral nutrition (PN). For all of them, gastrostomy was non-feasible. Patients were followed until death and monitored for complications. Results: PICC insertion was successful in all patients. Three months after insertion, the mean body weight increased by 4.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 15 publications
0
5
0
7
Order By: Relevance
“…Inflammation (phlebitis, edema) was reported in 0% to 17% of patients with PICCs 4,6,15,17,18,27,29,33,34,38,46,48 versus 17.5% with PIVCs reported in one study 6 and 0% to 23% with CICCs. 6,17,33 In the study by Griffiths and Philpot, 6 the number of insertion sites showing signs of phlebitis was significantly lower in critically ill patients using PICCs for venous access (17%) compared to PIVCs (65%), P < 0.01, but not compared to CICCs (22%).…”
Section: Safety Outcomesmentioning
confidence: 89%
See 2 more Smart Citations
“…Inflammation (phlebitis, edema) was reported in 0% to 17% of patients with PICCs 4,6,15,17,18,27,29,33,34,38,46,48 versus 17.5% with PIVCs reported in one study 6 and 0% to 23% with CICCs. 6,17,33 In the study by Griffiths and Philpot, 6 the number of insertion sites showing signs of phlebitis was significantly lower in critically ill patients using PICCs for venous access (17%) compared to PIVCs (65%), P < 0.01, but not compared to CICCs (22%).…”
Section: Safety Outcomesmentioning
confidence: 89%
“…33 The rate of catheter mechanical failure was 5% to 22.3% with PICCs 6,15,18,27,44 and 16% and 11% in PIVCs and CICCs, respectively, in a single study. 6 The percentage of patients experiencing venous thrombosis was 0% to 27.2% with PICCs 4,5,10,12,13,15,16,18,20,26,29,31,33,35,37,38,44,48,49 compared to 3.4% with PIVCs reported in one study 10 and 0% to 9.6% with CICCs. 5,16,17,33 In the study by Bonizzoli et al 16 in which catheters were used for prolonged IV therapy in patients discharged from the intensive care unit, rates of DVT were significantly higher for PICCs compared to CICCs (27.2% vs. 9.6% of patients or 7.7 vs. 4.4 DVTs per 1000 catheter days, P = 0.0007).…”
Section: Safety Outcomesmentioning
confidence: 89%
See 1 more Smart Citation
“…Several reports have addressed the usefulness of PICCs in the context of malignancy, neuromuscular disease, or hematologic disease (Hashimoto et al, 2017;Juntas-Morales et al, 2017;Park et al, 2016). In addition, previous research has shown that PICC insertion is a relatively low-risk procedure compared with CVC insertion (Brass et al, 2015;Saugel et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with conventional central venous catheters (CVCs), PICCs are less invasive at insertion and less likely to lead to infection (Chrisman et al, 1999; Safdar & Maki, 2005). PICCs are versatile and can be used short- to long-term, from acute to palliative care, and in patients with a variety of underlying conditions, including malignancy, inflammatory bowel disease, amyotrophic lateral sclerosis, and hematologic diseases (Hashimoto et al, 2017; Juntas-Morales et al, 2017; Park et al, 2016). As used in the treatment of various diseases, PICCs also could be a useful option during the treatment of elderly patients with dementia, although to our knowledge, no currently available reports have addressed.…”
Section: Introductionmentioning
confidence: 99%